Muatan HOTS Pada Latihan Soal Buku Bahasa Arab Madrasah Aliyah Kelas X Terbitan Quadra 2022 - Masrifah, Khusnul; Ahsanuddin, Mohammad; Mahliatussikah, Hanik; Ismail, Zawawi (Al-Lisan: Jurnal Bahasa, 2025)
Background: In today’s era, where critical thinking and problem-solving are vital competencies, the integration of Higher Order Thinking Skills (HOTS) into educational resources, particularly textbooks, has become an important benchmark for quality learning. Aims: This study aims to identify HOTS exercises in Arabic textbooks of Madrasah Aliyah class X published by Quadra in 2022 in terms of Bloom's revised taxonomy theory at the cognitive level of C4, or Analysing, C5, Evaluating, and C6 Creating. Methods: This research employs document analysis techniques (content analysis) within a qualitative descriptive approach to examine the object in depth using primary data. The researcher directly observed the book's content and analysed the HOTS elements in the exercise questions. These were then categorised according to the levels of the revised Bloom's Taxonomy, and conclusions were drawn based on the classifications. Results: The results reveal that although HOTS elements are present in each theme, they are relatively few. The distribution shows C4 (2.4%), C5 (5.2%), and C6 (9.1%), indicating a predominance of LOTS (Lower Order Thinking Skills) over HOTS. Implications: The findings imply the need for improvement and development of question exercises in Arabic textbooks to include aspects of higher order thinking skills (HOTS), especially at the C4 (analyze), C5 (evaluate), and C6 (create) levels, in order to support more critical, analytical, and creative learning in accordance with the demands of the 21st century curriculum.